The influence of nickel ions on the electric behaviour of P2O5–ZnO–Na2O glassy system. Issue 3 (3rd July 2019) - Elbashar, Yahia H.; Moslem, Shymaa S.; Rayan, Diaa A.; Hassan, Hussam H.
Abstract: P2 O5 –ZnO–Na2 O glasses doped with various concentrations of NiO in the range from 0 to 6 mol % are prepared. The measurements of the electric properties of the samples are studied at different temperatures and frequencies. It is found that the dielectric constant decreases with increasing frequency as well as the electric modulus shows relaxation behaviour. The effect of different NiO concentrations and their chemical states in the glass network appears in the analysis of the activation energy, where Ni 2+ ions have octahedral and tetrahedral states. From the frequency exponent result, the present samples exhibit correlated barrier hopping (CBH) conduction mechanism. The results show that some samples have great dielectric properties.